Barriers and facilitators associated with HIV testing uptake in South African health facilities offering HIV Counselling and Testing - Neo Mohlabane; Bomkazi Tutshana; Karl Peltzer; Aziza Mwisongo (AOSIS, 2016)
Background: The scale-up of HIV Counselling and Testing (HCT) in South Africa to 4500 public health facilities and the service's provision in mobile and non-medical sites was aimed at increasing HCT uptake. However, some people still have never had an HIV test. Objective: An HCT survey was carried out to ascertain barriers and facilitators for HIV testing in South Africa. Methods: A cross-sectional survey of 67 HCT-offering health facilities in 8 South African provinces was undertaken. Individuals (n = 489) who had not tested for HIV on the day of the site visit were interviewed on awareness of HCT services, HIV testing history and barriers to HIV testing. Frequencies were run to describe the sample characteristics, barriers and facilitators to HIV testing. Bivariate and multivariate logistic regression was usedt o identify the association between never tested for HIV with socio-demographics, awareness of HCT services and type of HCT facilities. Results: In all 18.1% participants never had an HIV test. Major barriers to HCT uptake comprise being scared of finding out one's HIV test result or what people may say, shyness or embarrassment, avoidance of divulging personal information to health workers and fear of death. In multivariate analysis the age group 55 years and older, and not being recommended to have an HIV test were associated with never had an HIV test. Potential facilitators for HIV testing include community or household HIV testing, providing incentives for those who test for HIV, mandatory HIV testing and disclosure of HIV status by those who test HIV positive. Conclusion: The benefits of HCT which include the reduction of HIV transmission, the availability of HIV care and treatment needs to be emphasized to enhance HCT uptake.